Brugada syndrome with a novel missense mutation in SCN5A gene: a case report from Bangladesh - Sayeed, Md. Zahidus; Salam, Md. Abdus; Haque, Md. Zahirul; Islam, A.K.M. Monwarul (Elsevier, 2014)
Brugada syndrome is an inherited cardiac arrhythmia that follows autosomal dominant transmission and can cause sudden death. We report a case of Brugada syndrome in a 55-year-old male patient presented with recurrent palpitation, atypical chest pain and presyncope. ECG changes were consistent with type 1 Brugada. Gene analysis revealed a novel missense mutation in SCN5A gene with a genetic variation of D785N and a nucleotide change at 2353G-A. One of his children also had the same mutation. To our knowledge this is the first genetically proved case of Brugada syndrome in Bangladesh.